2019
DOI: 10.1002/ptr.6312
|View full text |Cite
|
Sign up to set email alerts
|

Effect of turmeric on glycemic status, lipid profile, hs‐CRP, and total antioxidant capacity in hyperlipidemic type 2 diabetes mellitus patients

Abstract: Diabetes mellitus is the most common metabolic disorder worldwide. This study examined the effect of turmeric supplementation on glycemic status, lipid profile, hs-CRP and total antioxidant capacity in hyperlipidemic type 2 diabetic patients.In this double-blind, randomized clinical trial, 80 hyperlipidemic type 2 diabetic patients were divided into turmeric (2,100 mg powdered rhizome of turmeric daily) and placebo groups for 8 weeks. Body weight, fasting plasma glucose, hemoglobin A1c (HbA1c), serum insulin, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
75
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(79 citation statements)
references
References 35 publications
3
75
0
1
Order By: Relevance
“…A recent intervention study showed that 1500 mg/day curcumin supplementation (500 mg capsules: 347 mg of curcumin, 84 mg of demethoxycurcumin, and 9 mg of bisdemethoxycurcumin) for 10 weeks reduced triglycerides (TG) and C-reactive protein (CRP), and increased adiponectin levels [ 42 ], whereas 500 mg/day curcumin co-administered with piperine 5 mg/day for three months was able to reduce blood glucose, C-peptide, glycated hemoglobin (HbA1c), alanine aminotransferase (ALT) and aspartate aminotransferase (AST), in patients with T2D [ 43 ]. Another study showed that the daily ingestion of 2100 mg turmeric powder for eight weeks resulted in a reduction in body weight, low density lipoprotein-cholesterol (LDL-c), and TG levels, with no significant effects on glycemia, CRP, and HbA1c, in hyperlipidemic T2D patients [ 44 ]. In obese women with polycystic ovary syndrome (PCOS), 1000 mg/day curcumin supplementation (500 mg twice daily: 70–80% curcumin, 15–20% demethoxycurcumin and 2.5–6.5% bisdemethoxycurcumin) for six weeks improved serum insulin and the Quantitative Insulin Sensitivity Check Index [ 45 ].…”
Section: Role Of Curcumin In Pregnancymentioning
confidence: 99%
“…A recent intervention study showed that 1500 mg/day curcumin supplementation (500 mg capsules: 347 mg of curcumin, 84 mg of demethoxycurcumin, and 9 mg of bisdemethoxycurcumin) for 10 weeks reduced triglycerides (TG) and C-reactive protein (CRP), and increased adiponectin levels [ 42 ], whereas 500 mg/day curcumin co-administered with piperine 5 mg/day for three months was able to reduce blood glucose, C-peptide, glycated hemoglobin (HbA1c), alanine aminotransferase (ALT) and aspartate aminotransferase (AST), in patients with T2D [ 43 ]. Another study showed that the daily ingestion of 2100 mg turmeric powder for eight weeks resulted in a reduction in body weight, low density lipoprotein-cholesterol (LDL-c), and TG levels, with no significant effects on glycemia, CRP, and HbA1c, in hyperlipidemic T2D patients [ 44 ]. In obese women with polycystic ovary syndrome (PCOS), 1000 mg/day curcumin supplementation (500 mg twice daily: 70–80% curcumin, 15–20% demethoxycurcumin and 2.5–6.5% bisdemethoxycurcumin) for six weeks improved serum insulin and the Quantitative Insulin Sensitivity Check Index [ 45 ].…”
Section: Role Of Curcumin In Pregnancymentioning
confidence: 99%
“…Moreover, it has been indicated hypolipidemic effects of turmeric and curcumin [15,16]. And it has been found the effect to decrease the cholesterol level in humans [17] and in rabbits which suggested the role to manage the cardiovascular disease [12]. Furthermore, it has been indicated the beneficial role of turmeric extract in other diseases and disorders including obesity, diabetes and liver disease [18][19][20][21]; whereas to the anti-inflammatory effects the immune system [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…However, direct anti-atherosclerosis activity of preparations based on garlic powder was studied wider than others natural products, their ameliorating effect on the progression of cIMT was proved in randomized double-blinded placebo-controlled trials, registrated on https://clinicaltrials.gov/ (Hodis et al, 2011;Mahdavi-Roshan et al, 2013;Karagodin et al, 2016aKaragodin et al, 2016b. Garlic preparations have the most interesting and obvious cardio-protective properties since garlic is able to ameliorate the blood lipids profile by inhibiting cholesterol biosynthesis, reducing of LDL, modulate arterial hypertension, and inhibit platelet aggregation (Sobenin et al, 2008a;Sobenin et al, 2008b;Sobenin et al, 2009;Jung et al, 2014;Mahdavi-Roshan et al, 2016;Myasoedova et al, 2016;Villa et al, 2017;Choudhary et al, 2018;Sathyapalan et al, 2018;Panahi et al, 2018;Xu et al, 2018;Sedaghat et al, 2019;Adibian et al, 2019;Adab et al, 2019). In laboratory experiments, garlic extract inhibits proliferative and inflammatory cellular reactions, possesses anti-cytokine properties, has pronounced antioxidant activity, so reduces the oxidation of LDL, activates the hydralase of cholesterol esters and inhibit ACAT, so reduces the content of cholesterol esters in cells.…”
Section: Resultsmentioning
confidence: 99%
“…et al, 2019). Adab Z et al have demonstrated that administration of turmeric (2,1 g powdered rhizome of turmeric daily for 8 weeks) significantly decreased BMI as well as plasma Tg, TC, and LDL (Adab et al, 2019). Panahi Y et al also observed lipid-lowering effect in their randomized controlled trial using curcuminoids (1 g/ day plus piperine 10mg/day) treatment of diabetes patients for 12 weeks (Panahi et al, 2018).…”
Section: Effectmentioning
confidence: 99%
See 1 more Smart Citation